2020
DOI: 10.1186/s12911-020-01162-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of an algorithm to detect and reduce complexity of drug treatment and its technical realisation

Abstract: Background: The increasing complexity of current drug therapies jeopardizes patient adherence. While individual needs to simplify a medication regimen vary from patient to patient, a straightforward approach to integrate the patients' perspective into decision making for complexity reduction is still lacking. We therefore aimed to develop an electronic, algorithm-based tool that analyses complexity of drug treatment and supports the assessment and consideration of patient preferences and needs regarding the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Is it difficult for you to use this drug always at the same day of the week?" for the complexity factor once weekly administration) [5]. If the patient indicated to experience any difficulties, the complexity factor was considered to be relevant for the patient in the analysis.…”
Section: Relevance Of the Complexity Factors In Patients Included In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Is it difficult for you to use this drug always at the same day of the week?" for the complexity factor once weekly administration) [5]. If the patient indicated to experience any difficulties, the complexity factor was considered to be relevant for the patient in the analysis.…”
Section: Relevance Of the Complexity Factors In Patients Included In ...mentioning
confidence: 99%
“…To integrate the patient's assessment of prevalent complexity, we have previously developed an electronic tool that combines an automated analysis of complexity of drug treatment with an individual assessment of the relevance of each complexity factor for the respective patient [5]. The electronic tool considers 38 complexity factors that can be identified automatically in structured medication data and can be assigned to one of the following categories: dosage form, dosage scheme, process characteristics, product characteristics, and additional instructions.…”
Section: Introductionmentioning
confidence: 99%
“…One participant suggested that prescribers could use MRS GRACE to guide simplification when preparing new medication charts as a potential point for future intervention. Previous studies in other settings have utilized screening tools, algorithms and/or electronic medication chart prompts to identify individuals with complex medication regimens [ 37 , 38 , 39 ]. Additionally, in the Australian state of Victoria, a medication quality indicator ‘percentage of residents with more than four medication administration times’ was developed, validated and implemented across all 180 public-sector RACFs as a prompt to reduce unnecessary complexity [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The tool was exploratively evaluated in a controlled, prospective, pilot study with general practitioners (GP) allocated to three study groups. Group 1 (G I_with ) used the full version of the tool [ 11 ], while group 2 (G I_without ) used a version of the tool with limited functionality that did not propose key questions and, therefore, lacked personalization of the automated results. Group 3 (G C ) was a control group representing routine care where physicians did neither receive a training in complexity reduction nor use any version of the tool.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, an electronic tool was developed that is applied by health professionals but attempts to comprehensively consider the patient perspective [ 11 ]. It automatically screens structured medication data for 38 known factors contributing to complexity (automated assessment).…”
Section: Introductionmentioning
confidence: 99%